Push and pull factors influencing travel desire and revenge tourism intention in Malaysia post covid19 - Tan, Jia Huei (2022)
This research intends to find out what influencing peoples’ travel desire and revenge tourism intention in Malaysia post Covid-19. Tourism industry is the most affected industry due to the Covid-19 pandemic; it has been completely shut down since the beginning of the pandemic. Meanwhile, tourism industry is the major contributor of GDP to the whole world especially in Malaysia. Thus, it is a significant industry which needed to be revive. It is important to know what factors will influencing people to travel in Malaysia post Covid-19. The purpose of this research is to investigate the push and pull factors influencing travel desire and revenge tourism in Malaysia post Covid-19. This research is studying the relationship between independent variables which as push factor (novelty and knowledge seeking, ego enhancement, rest and relaxation), pull factor (environment and safety, cultural and historical attractions, tourism facilities) and dependent variables which is travel desire and revenge travel intention. The results of this research can be used to define how push and pull factor influencing travel desire and revenge tourism in Malaysia post Covid-19. In this research, data are collected by distributing self-administered questionnaire. Both Software Package for Social Sciences (SPSS) is used to perform descriptive analysis and analysed data has been illustrated in pie charts, summaries, central measures of tendencies. Whereas, SmartPLS is adopted to perform Partial Least Square Structural Equation Modelling (PLS-SEM) analysis, including measurement and structural model. Implications of study and recommendations for future researchers have been pointed out before concluding the whole research. To sum up, this research may provide insightful information to Malaysian government, policymakers and managers in tourism industry for a better understanding of the push and pull factor influencing travel desire and revenge tourism in Malaysia post Covid-19.